DETERMINAN AUDIT REPORT LAG (STUDI EMPIRIK PADA PERUSAHAAN LQ-45 TAHUN 2014-2018) - Adibah Yahya (AKUNTANSI DEWANTARA, 2020)
The company's financial performance for each period is always reported in the form of audited financial reports, especially for companies listed on the Indonesia Stock Exchange (IDX). In the submission of the audit report, there is a time difference between the end of the fiscal year and the date of issuance of the audit report, which is called the audit report lag. The factors that affect the audit report lag include company size (Size), Return On Assets (ROA), Financial Distress (FD) and the size of the Public Accounting Firm (KAP). This study aims to determine the effect of these factors on the audit report lag (ARL). The research method used in this research is multiple linear regression analysis method, with a sample of companies LQ-45 listed on the IDX in 2014-2018. The results of the analysis show that simultaneously Size, ROA, FD and KAP have an effect on ARL, while Size and KAP partially affects ARL, ROA and FD have no effect on ARL.